Indikator Penerapan Ham Universal Dan Ham Partikular Dalam Putusan Mk No 46/Puu-Viii/2010 Tentang Anak Di Luar Perkawinan Dan Putusan Mk No 8/Puu-Xii/2014 Tentang Perkawinan Beda Agama - Hanif Millata Ibrahim (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2018)
This research presents there are at least, three differences due to Human Rightsimplemention in this two verdicts; the lawsuit object and the interpretation model ofConstitution and constitutional courts tends to apply contextual understanding in the order of MK No. 46/PUU-VIII/2010 and tends to apply textual understanding in the order of MK MK No. 8/PUU-XII/2014. While there are 5 indicators ofHuman Rights implementation. First, the interpretation of constitution should give a maximum protection to minorities. Second, it must accomodate a relevant international covenant and it’s not yet regulated in legislation. Third, it must protect it constitutional rights of civilian. Fourth, to recover the violated constitutional rights. Fifth, it should be formed by technology developments, economic aspect, global socio-cultural that is not contradicted to fundamental principles of Pancasila.